Pengaruh Pemanfaatan E-learning dan Self Regulated Learning Terhadap Prestasi Belajar Mahasiswa Fakultas Ekonomi Universitas Negeri Padang Di Masa Pandemi Covid-19 - Derri Aprino; Tri Kurniawati (Universitas Negeri Padang, 2022)
The emergence of the COVID-19 pandemic has had a negative influence on education. The purpose of this study is to analyze the impact of the use of e-learning and self-regulated learning on student achievement at the Faculty of Economic. Universitas Negeri Padang This is quantitative research with a descriptive method. Questionnaires and documentation are used to collect data. The proportional random sampling technique was used in this research, with a total sample size of 85 respondents. The data analysis technique used in this study is path analysis. The findings of this study show that : 1) The use of e-learning has a positive and significant effect on self-regulated learning, 2) The use of e-learning has a positive and significant effect on student achievement, 3) Self-regulated learning has a positive and significant effect on student achievement. Keywords: the use of e-learning, self-regulated learning, student achievement